The Impact of Banking Competition on Economic Growth and Financial Stability: An Empirical Investigation - Abuselidze, George (European Journal of Sustainable Development, 2021)
The paper examines the level of competition in banking market using different econometric models and analyzes the impact of efficiency of the banking system on the economic growth of the country. The research discusses to ensure banking competition as a function of the Central Bank. Also, the paper includes some recommendations developed to improve banking competition. Our hypothesis is that the existence of high levels of banking competition and low concentration in the banking market balances the speed of money supply in the economic sector. As a result, the Central Bank’s monetary policy will be more effective in achieving its core objectives. Therefore, banking competition contributes to the economic growth of the country. In addition, the monetary policy of the Central Bank concentrates on financial stability, which is one of the fundamental factors in the economic development of a country.